On coprimely packed rings - TEKİR, ÜNSAL (TAYLOR & FRANCIS INC, 2007)
Let R be a coprimely packed ring and S a multiplicatively closed subset of R. In this article we investigate conditions under which S-1 R is a coprimely packed. It is also proved that if R is a Noetherian integrally closed domain, then R[X] is a coprimely packed ring if and only if R is a semilocal principal ideal domain.
Keywords: coprimely packed rings; noetherian rings; polynomial rings; POLYNOMIAL-RINGS; IDEALS